Case Report: Menstrual cycle–related psychosis in bipolar I disorder, remitting with a combined oral contraceptive - Hanyu, Shota; Yoshimoto, Kei; Shimizu, Nobuo (Frontiers in Psychiatry, 2025)
Menstrual cycle–related psychosis is a rare condition presenting with recurrent affective and psychotic symptoms temporally linked to the menstrual cycle. We report a case with two uncommon features: paradoxical relapse during antipsychotic-induced amenorrhea with hyperprolactinemia, and sustained remission after adjunctive hormonal stabilization using a combined oral contraceptive (drospirenone–ethinyl estradiol). Although phenomenology overlaps with bipolar disorder, the regular monthly periodicity and frequent premenstrual onset indicate a menstrual cycle–related substrate. Rigorous differentiation from bipolar disorder is therefore essential to avoid misclassification and to guide treatment, including consideration of endocrine modulation when this pattern is evident. We describe a 19-year-old Japanese woman with no psychiatric history who presented with acute mania and psychosis necessitating hospitalization. Despite treatment with antipsychotics and mood stabilizers for a bipolar-spectrum illness, she experienced recurrent monthly relapses tightly linked to menstruation, and prophylaxis could not be achieved. During higher-dose antipsychotic therapy, she developed amenorrhea with marked hyperprolactinemia; however, psychotic relapse occurred even during the amenorrheic period. To stabilize ovarian hormones, a combined oral contraceptive was initiated. Premenstrual exacerbations progressively attenuated and then ceased over four months, permitting simplification to the minimum effective antipsychotic regimen. She remained well for an extended period on maintenance psychiatric pharmacotherapy together with the combined oral contraceptive. This case suggests that menstrual cycle–related psychosis may reflect sensitivity to hypoestrogenism: relapse occurred during antipsychotic-induced amenorrhea, whereas adjunctive treatment with a combined oral contraceptive was associated with sustained remission. Adjustments of antipsychotics and mood stabilizers afforded at most transient benefit and did not prevent relapses or attenuate peak severity; sustained improvement occurred only after continuous drospirenone–ethinyl estradiol. For patients who show clear cycle-linked exacerbations despite antipsychotics and mood stabilizers, endocrine stabilization with a combined oral contraceptive may be considered. Operationally, we coded the case as Bipolar I disorder (DSM-5-TR/ICD-11) based on a syndromal manic episode, while phenotypically it showed a menstrual cycle–related (catamenial) pattern—regular cycle-linked, perimenstrual exacerbations with complete inter-episode remission—distinguishing it from non-catamenial bipolar and other psychotic disorders.